Contact force with magnetic-guided catheter ablation. (1st May 2018) - Bessière, Francis; Zikry, Christopher; Rivard, Lena; Dyrda, Katia; Khairy, Paul
Abstract: Aims: Achieving adequate catheter tip-tissue contact is essential for delivering robust radiofrequency (RF) ablation lesions. We measured the contact force generated by a remote magnetic-guided catheter navigation system. Methods and results: A plexiglass model with an integrated scale was fashioned to mimic transvenous and retrograde access to sites in the right atrium and right and left ventricles. An 8 Fr RF ablation catheter was steered by remote magnetic guidance at fields of 0.08 and 0.10 T, with and without a long sheath positioned at the entrance of the chamber. Ten contact force readings were taken at each setting, with the scale recalibrated prior to each measurement. Generalized estimating equations were used to compare contact force measurements while adjusting for the non-independent data structure. A total of 240 contact force measurements were taken. Without a long sheath, contact forces with magnetic fields of 0.10 T ( n = 60) and 0.08 T ( n = 60) were similar (6.1 ± 1.4 g vs. 6.0 ± 1.3 g, P = 0.089). Contact forces were not significantly different with simulated transvenous ( n = 80) and retrograde aortic ( n = 40) approaches (6.2 ± 1.4 g vs. 5.7 ± 1.2 g, P = 0.132). The contact force increased substantially with a long sheath (P < 0.001) and was significantly higher with 0.10 T ( n = 60) vs. 0.08 T ( n = 60) fields (20.4 ± 0.6 g vs. 18.0 ± 0.5 g, P < 0.001). Conclusion: Magnetic fields of 0.08 and 0.10 T provide stable catheter contact forces, as reflected by the small variability between measurements. The average contact force is approximately 6 g without a sheath and increases to 20 g with a long sheath positioned at the entrance of the chamber of interest.